A Temperature Rise Calculation Method of Gear Transmission Considering Variation of Physical Parameter with Temperature - Chang Li; Zhibin Yu; Yunfei Li; Yuxuan Chen; Xing Han (Jixie chuandong)
The high speed and heavy load gear meshing transmission will cause temperature rise because of friction and heat. The gear will produce thermal expansion and cause meshing error, which makes the vibration and noise increase, and then aggravate the process of failure of gluing. Therefore, it is significant to calculate the temperature rise and analyze the influencing factors of gear transmission. The temperature rise will lead to the change of gear thermal physical property parameters and affect the temperature field. If this effect is ignored, an error will be generated. Based on involute spur gear, according to gear meshing theory and friction heat transfer principle, the instantaneous friction heat flow and convection heat transfer coefficient in the transmission process of gear are calculated and solved. The CALPHAD method is used to calculate the physical parameters at different temperatures. Based on the ANSYS thermosetting coupling calculation method, the calculation program under the variable physical parameters is compiled by APDL, the temperature rise of the gear transmission is calculated, and the change of temperature field in the gear transmission process is obtained. A parametric solution program is written, and the influence of tooth width and torque parameters on the temperature rise of meshing transmission is analyzed. The research provides an important basis for analyzing the influence mechanism of temperature rise on gear failure, and has certain guiding significance.